PENGARUH PENGEMBANGAN KARIR DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN HOTEL TJOKRO PEKANBARU - Jodi Bagaskoro; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the effect of career development and organizational commitment on employee performance at Hotel Tjokro Pekanbaru. This research is located at Hotel Tjokro Pekanbaru. The population in this study includes employees of the Tjokro Pekanbaru Hotel in 2020, totaling 43 employees. The sample used is the census technique. Data analysis used statistical analysis with the help of SPSS. Data collection techniques used are questionnaires and interviews. Data testing techniques in this study include validity test, reliability test, simple linear regression analysis, multiple linear regression analysis, coefficient of determination test, t-test and f-test to test and prove the hypothesis. The results of the study indicate that Career Development and Organizational Commitment have an influence on Employee Performance at Tjokro Hotel Pekanbaru. Based on the results of the study, obtained an R Squere value of 0.401, meaning that 40% of career development variables and organizational commitment have an effect on employee performance at Tjokro Hotel Pekanbaru.   Keywords: Career development, organizational commitment, employee performance